A mini-review on household solid waste management systems in low-income developing countries: A case study of urban Harare City, Zimbabwe. Issue 2 (February 2022) - Kwenda, Phyllis Rumbidzai; Lagerwall, Gareth; Eker, Sibel; Van Ruijven, Bas
Among other African cities, in terms of solid waste management (SWM), Harare has been ranked as one of the poorest. The municipality struggles to efficiently provide SWM services to its residents. Considering that SWM systems are complex, the individual behaviour of its components (waste generation, collection, and disposal) determines the overall performance of the system. This mini-review thus aims to understand the management system of the urban city's biggest source of solid waste which is household solid waste (HSW). The systematic literature review methodology using NVIVO was used to analyse the literature. Out of a selected sample size of 500 journal articles, 26 were selected based on their relevance to the study. The uncertainty of the data provided by the Harare City Council (HCC) and of HSW generation data harvested in the literature was calculated. According to the HCC data records, Harare has an average daily waste generation per capita of on average 0.38±0.1 kg producing about 207, 635, 294±56, 027, 040 kg of HSW generated annually. With the waste collection efficiency in Harare at about 72.4%±7.5%, the city collects approximately 170, 385, 600±33 384 209 kg of HSW annually. All the collected HSW is disposed of in the city's major MSW dumpsite called Pomona and only about 23, 498, 400±3, 988, 817 kg MSW is recovered annually with the average recovery efficiency at around 9.5%±2.8%, where most of the waste recovery is done by the waste pickers.